2017
DOI: 10.5038/1936-4660.10.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Scientific and Numerate Practices in Journalism to Support Rapid Public Learning

Abstract: Journalism has the potential--and arguably the mandate--to expand public understanding of societally important phenomena. However, some methods for more effectively educating the public have been persistently underutilized: in particular, embedding informative numerical rates and efficient scientific explanations in news reports. In the current era of disrupting and downsizing the news business, the challenges to using such methods have only increased. To address this problem, this article seeks to (a) raise a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…To assess the mechanism behind this improvement, a researcher who was blind to each student's class (i.e., control vs. intervention) interviewed volunteers from each group several months after the curriculum and found greater richness in the strategies employed by the intervention class on novel items (Ganpule, ). Collectively, these findings, and similar findings with graduate journalism students (Ranney et al., ; Yarnall & Ranney, ), indicate that learners can internalize the consideration of alternatives, and learn to process social and personal issues more systematically, in the course of a relatively brief intervention (e.g., 12% of a 10‐week class time for high school students). Once one has internalized this process, one might spontaneously invoke alternative possible outcomes to avoid hindsight bias, embrace cognitive difficulty as a chance to enrich one's belief network, and, as one's network grows in richness, develop the ability to appropriately reject anomalies.…”
Section: Internalizing Use Of the Surprise Signalsupporting
confidence: 71%
“…To assess the mechanism behind this improvement, a researcher who was blind to each student's class (i.e., control vs. intervention) interviewed volunteers from each group several months after the curriculum and found greater richness in the strategies employed by the intervention class on novel items (Ganpule, ). Collectively, these findings, and similar findings with graduate journalism students (Ranney et al., ; Yarnall & Ranney, ), indicate that learners can internalize the consideration of alternatives, and learn to process social and personal issues more systematically, in the course of a relatively brief intervention (e.g., 12% of a 10‐week class time for high school students). Once one has internalized this process, one might spontaneously invoke alternative possible outcomes to avoid hindsight bias, embrace cognitive difficulty as a chance to enrich one's belief network, and, as one's network grows in richness, develop the ability to appropriately reject anomalies.…”
Section: Internalizing Use Of the Surprise Signalsupporting
confidence: 71%
“…Prior classroom and laboratory studies have demonstrated the impact of presenting people with surprising numbers about controversial topics on their understanding of social issues (for reviews, see Ranney et al, 2019;Yarnall & Ranney, 2017). Many of these studies are grounded in a paradigm called "Numerically Driven Inferencing" (NDI; Ranney & Thagard, 1988;Ranney et al, 2001), which assumes that individuals' understanding of numerical information is connected to their knowledge, attitudes, and beliefs about larger issues.…”
Section: An Existing Learning Intervention: Epicmentioning
confidence: 99%
“…Perception of this knowledge void is attenuated by surprise-and thus, it is the most surprising numbers and stories that have the most potential to spawn considerable cognitive change and belief revision (Ranney & Clark, 2016). It has also been found that the more surprised people are by numbers, the less knowledgeable they report feeling about an issue, and thus, the more open they are to changing their beliefs in line with the number--a phenomenon known in the media as the establishing effect (Yarnall & Ranney, 2017). This is illustrated by the fact that participants who were surprised by the immigration rate in the 2001 experiment, for instance, were four times more likely to significantly change their positions on the issue than those participants who were less surprised (Ranney et al, 2001).…”
mentioning
confidence: 99%